Stability of activity space footprint, size, and environmental features over six months. (August 2019) - Kraft, Amber N.; Jones, Kelly K.; Lin, Ting-Ti; Matthews, Stephen A.; Zenk, Shannon N.
Highlights: This study compared GPS-derived measures of activity-space footprint, size, and environmental features at baseline and approximately six months later. Activity-space footprint, size, and environmental features were moderately to highly stable over time. Temporal stability varied considerably between measures. Temporal instability may increase measurement error, making it difficult to detect associations between activity-space environmental features and health outcomes. Abstract: As activity space measures are increasingly used to estimate exposure to environmental determinants of health, little is known about the stability of these measures over time. To test the stability of GPS-derived measures of activity-space footprint, size, and environmental features over time, we compared 14-day measures at baseline and six months later for 35 adults in a large city. Activity-space measures were based on convex hulls and 500 m route buffers, and included the geographic footprint (i.e. location of the activity space), size (i.e., area in square miles; (Cummins, 2007 )), and environmental features including supermarket, fast-food restaurant, and parkland density. The proportion of the participants' smaller geographic footprint covered by the larger was, on average, 0.64 (SD 0.17) for the 500 m route buffer and 0.84 (SD 0.18) for the convex hull. Mean percent change in activity space size ranged from 36.3% (mean daily 500 m route buffer) to 221.3% (cumulative convex hull). Mean percent change in the density of environmental features ranged from 28.8 to 66.5%. Forty-one percent to 92.4% of the variance at one timepoint was predicted by environmental features measured within approximately six months. Activity-space size and environmental features were moderately to highly stable over six months, although there was considerable variation in stability between measures. Strategies for addressing measurement error in studies of activity space-health associations are discussed.